Penerapan Model Take and Give untuk Meningkatkan Keterampilan Kerjasama dan Hasil Belajar Siswa pada Pembelajaran Agama Islam Di Kelas V SDN 009 Bengkulu Utara - Sutinah Sutinah (Journal of Elementary School (JOES), 2020)
This study aims to prove whether the application of the Take And Give learning model can improve student work skills and student learning outcomes. This study used a classroom action research design with four stages of research, namely the planning stage, the implementation stage, the observation stage, and the reflection stage. The subjects of this study were students of class V SD Negeri 009 Bengkulu Utara which consisted of 20 students. The results showed that the application of the Take And Give learning model was proven to be able to improve students 'cooperation skills where in the initial ability test phase, the percentage of students' cooperation skills was 30%, increased in cycle I by 55% and increased in cycle II by 80%. The application of the Take And Give learning model is also proven to be able to improve student learning outcomes where in the initial test phase of students' classical completeness levels of students by 35%, increasing in cycle I to 60% and in cycle II increasing to 100%. In conclusion, the application of the Take And Give learning model is effective in improving student cooperation skills and student learning outcomes at SDN 009 Bengkulu Utara. Keywords: Learning Outcomes, Cooperation Skills, Take And Give